Kontribusi layanan informasi dalam konseling dan kedisiplinan siswa terhadap prestasi belajar siswa - Sri Utami (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
This research aimed to find out (1) the influence of information service in counseling and student discipline towards the student learning achievements, (2) the influence of information service in counseling toward student learning achievement and (3) the influence of student discipline against students learning achievements. This research using quantitative research with regression techniques. This research was conducted at the Vocational School (SMK) in Depok with population of 824 students. The sample in this study are 80 students who were taken as a proportional random sampling. The results of this research showed (1) there is a significant influence of information service in counseling and students discipline together against the student learning achievement, (2) there are significant effects of information service in counseling toward the accomplishment of learning, and (3) there is a significant influence of the student discipline against student achievement learning.